2012
DOI: 10.1177/030006051204000511
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Symptoms and Gastric Emptying of Solids in Functional Dyspepsia

Abstract: OBJECTIVE: Functional dyspepsia is a heterogeneous disorder and different pathophysiological mechanisms underlie its symptom patterns. This study investigated the relationship between dyspepsia symptoms and overall and proximal gastric emptying in patients with functional dyspepsia. METHODS: A total of 93 patients with functional dyspepsia and 32 healthy subjects were enrolled in this cross-sectional study. Prevalence and severity of eight dyspepsia symptoms were recorded. Gastric emptying was measured using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
(49 reference statements)
2
16
0
Order By: Relevance
“…4,5 Although population-based studies found a good separation between PDS and EPS, patient samples showed up to 50% overlap between both, thereby limiting the usefulness of this subdivision in clinical practice. [10][11][12][13][14][15][16][17][18][19][20] In this study, we confirmed the major overlap between EPS and PDS in a group of 199 consecutive newly diagnosed FD patients. We evaluated in detail the relationship of symptoms to meal ingestion, and this revealed a high proportion of postprandially occurring non-PDS symptoms (epigastric pain and nausea) in the overlapping EPS-PDS group, compared with the pure EPS group.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…4,5 Although population-based studies found a good separation between PDS and EPS, patient samples showed up to 50% overlap between both, thereby limiting the usefulness of this subdivision in clinical practice. [10][11][12][13][14][15][16][17][18][19][20] In this study, we confirmed the major overlap between EPS and PDS in a group of 199 consecutive newly diagnosed FD patients. We evaluated in detail the relationship of symptoms to meal ingestion, and this revealed a high proportion of postprandially occurring non-PDS symptoms (epigastric pain and nausea) in the overlapping EPS-PDS group, compared with the pure EPS group.…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with the presumed heterogeneity of FD, the ROME III consensus proposed to subdivide patients into two categories: meal‐related PDS symptoms including postprandial fullness and early satiation; and meal‐unrelated EPS symptoms characterized by epigastric pain and epigastric burning . Although population‐based studies found a good separation between PDS and EPS, patient samples showed up to 50% overlap between both, thereby limiting the usefulness of this subdivision in clinical practice …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature review suggests this is the first study to demonstrate a strong correlation between symptoms and a motility parameter in gastroparesis using a duodenal—rather than gastric—motility measurement. Past studies have been limited to analysis of transit times such as gastric emptying by GES and have shown poor correlation with upper GI symptoms (1517). In this study, we observed significant negative correlations, such that decreased contractile motility corresponded to increased symptom severity.…”
Section: Discussionmentioning
confidence: 99%